PENGARUH PEMBIAYAAN, DANA PIHAK KETIGA DAN NON PERFORMING FINANCING TERHADAP RETURN ON ASSETS PERBANKAN SYARIAH DI INDONESIA 2009-2013: PENERAPAN MODEL SIMULTAN - Atika Ranianti; Nirdukita Ratnawati (Jurnal Ekonomi Trisakti, 2022)
Sharia banking has been developed in Indonesia since 1991. Sharia banks have the same function as conventional banks, as intermediate financial institutions. They collects money from the society and then distribute the money by providing loans to get profits. However, the loans are not always current but sometimes they are sub standard, doubtful or even loss. This research is aimed to see the corelation among third party funds, distributed loans, Non performing loans and profitability of a sharia bank in Indonesia through its Return on Assets as the proxy. From the statistical data of the period 20091 - 2013.3 which is analyzed by a simultaneous-equation model, it is found that the third-party fund, Non Performing Funds and Return on Assets are correlated.